An Analytical Review of Dividend Policy Theories - Murtaza, Muhammad; Manzoor Iqbal, Malik; Ullah, Zia; Rasheed, Haroon; Basit, Abdul (Journal of Advanced Research in Business and Management Studies, 2020)
A storm had been brought in the unidirectional thinking regarding dividends since its evolution when Miller and Modigliani [54] put forward their proposition of dividend irrelevance. The storm further intensified as further theories added to the discussion. Based on their evidence different researchers have different opinions about dividend policy. However, despite the intensive literature on dividend policy in the last sixty years, still, the researchers are unable to achieve unanimity on a general dividend theory that can either explain the process of dividend decision making or forecast an ideal dividend policy. At this point, one is compelled to accept the term “Dividend Puzzle” introduced by Black [17] by saying, “The harder we look at the dividend picture, the more it seems like a puzzle, with pieces that just don’t fit together”.